2017
DOI: 10.1080/15548627.2016.1256932
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and KRT8/keratin 8 protect degeneration of retinal pigment epithelium under oxidative stress

Abstract: Contribution of autophagy and regulation of related proteins to the degeneration of retinal pigment epithelium (RPE) in age-related macular degeneration (AMD) remain unknown. We report that upregulation of KRT8 (keratin 8) as well as its phosphorylation are accompanied with autophagy and attenuated with the inhibition of autophagy in RPE cells under oxidative stress. KRT8 appears to have a dual role in RPE pathophysiology. While increased expression of KRT8 following autophagy provides a cytoprotective role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 65 publications
4
43
1
Order By: Relevance
“…Moreover, knockdown the expression or alteration of the critical phosphorylation site (Ser74) of KRT8 induced autophagy impairment, through affecting the fusion of autophagosomes and lysosomes. These results were inconsistent with the recent studies, in which phosphorylated KRT8 is always in parallel with the total KRT8 expression, and the latter facilitates the autophagic process and plays a protective role in RPE cells under oxidative stress . As demonstrated by previous reports, phosphorylation of IFs can modulate their interaction with IF‐related proteins, such as adaptor protein 14‐3‐3 .…”
Section: Discussioncontrasting
confidence: 80%
“…Moreover, knockdown the expression or alteration of the critical phosphorylation site (Ser74) of KRT8 induced autophagy impairment, through affecting the fusion of autophagosomes and lysosomes. These results were inconsistent with the recent studies, in which phosphorylated KRT8 is always in parallel with the total KRT8 expression, and the latter facilitates the autophagic process and plays a protective role in RPE cells under oxidative stress . As demonstrated by previous reports, phosphorylation of IFs can modulate their interaction with IF‐related proteins, such as adaptor protein 14‐3‐3 .…”
Section: Discussioncontrasting
confidence: 80%
“…It has also been demonstrated that KRT8 is increased in retinal pigment epithelium by oxidative stress, suggesting that its increase may be a potential cytoprotective mechanism against reactive oxygen species (ROS). 54 Considering that KRT8 was mainly up-regulated under abnormal or unhealthy conditions based on previous studies and our results, it is believed that up-regulation of Krt8 in response to chronic alcohol exposure may protect the hippocampus from oxidative stress triggered by alcohol. In addition, Vim was increased by chronic alcohol exposure in our study.…”
Section: Discussionsupporting
confidence: 57%
“…Knockdown of KRT8 in mice resulted in a reduced litter size and in the death of the pups at birth (Baribault, Price, Miyai, & Oshima, ). Besides, Baek et al () demonstrated that short‐term exposure to oxidative stress does not trigger cell death. Instead, triggers autophagy, upregulation of KRT8 and its phosphorylation to prevent apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%